AMELIORATE MANEUVER FOR TRANSFORMATION OF LACTOBACILLUS STRAINS BY ELECTROPORATION WITH IBDV-VP2 CHEMICALLY ENGINEERED EXPRESSION VECTOR - M. Iram; X. Wang; H. Y. Zhao; B. S. Mohsin; A. M. Nadeem; K. Saima; L.J. Tang; L. Y. Jing (Journal of Animal and Plant Sciences, 2016)
Lactobacillus competent cells are considered important vehicles for electro-transform process and express exogenous DNA. Previously several complex protocols were used for electro-transformation of lactobacillus strains. In the preset study, we evaluated an ameliorate maneuver for the preparation of efficient competent cells of lactobacillus. The parameters like (i) washing buffers (ii) optical density 600nm (O.D 0.4-0.5) (iii) plasmid concentration i.e. 2µl-6µl (100ng/µl) (iv) Voltage 2.3-2.4 kv/cm were mainly focused. The high transformation efficiency was recorded in  Lactobacillus casie393 (9.9×102 and 2.4×102), Lactobacillus pentosus (1.1×103and 3.1×102), Lactobacillus plantarum (1.2×103 and 3.7×102), with chemically engineered IBDV-vp2 expression plasmids viz., (i) pPG612-HCE-PgsA-vp2-rrnBT1T2, (ii) pPG612-HCE-T7g10-PgsA-vp2-rrnBT1T2 by electroporation. Further confirmation of electro-transformation was analyzed by isolation, digestion and PCR. Hence this method proved simpler and efficient among previously employed methods in the preparation of lactobacillus competent cells. Consequently this procedure makes lactobacillus strains an excellent candidate for electro-transformation, more over could be used for electro-transform of other lactobacillus delivery vectors.
Keywords: competent cell; IBDV-vp2; electroporation; lactobacillus; transformation; ameliorate maneuver